Pore‐scale modeling of microbial activity: What we have and what we need. Issue 1 (5th January 2021) - Golparvar, Amir; Kästner, Matthias; Thullner, Martin
Abstract: Under water‐unsaturated conditions, environmental factors (e.g., substrate, nutrients, O2, water activity, and porous structure) controlling microbial activity are highly variable in space and time. The physical structure of porous media (pore size distribution and pore arrangements) has been considered to have a significant role in nutrient (either substrate and/or its reaction partners like O2 ) fluxes. Understanding what eventually controls microbial activity thus requires a sound description of the physical and chemical conditions in the pore space down to the microscale, as well as knowledge on how microorganisms respond to the energy and matter fluxes in their microscale environment. Microscale modeling has the advantage to resolve the processes down to their fundamental level. In recent years, microscale models describing the physical setting in unsaturated porous media such as soils, as well as growth and functional performance of microorganisms, have become increasingly established and are supported by new experimental techniques resolving the distribution of solid, liquid, and gaseous phases at microscale resolution. Still, integration of these components for simulation of microbial activities in a soil system at the microscale is scarce. This mini‐review highlights the available approaches for pore‐scale modeling of flow and transport processes in both saturated and unsaturated porous media, and for modeling the dynamics of microbial activity constrained by different soil boundary conditions. Further, it is discussed what is required in terms of model development and improved modeling concepts to achieve a holistic reactive transport modeling approach describing microbial activity at the pore scale.